Relationships between physical fitness attributes, food habits and nutritional knowledge in youth basketball players - Sánchez-Díaz, S.; Marqués-Jiménez, D.; Castillo, D.; Izquierdo, J. M.; Yanci, J.; Raya-González, J. (SportMont, 2024)
Understanding food habits and nutritional knowledge in youth athletes could contribute to optimal recovery and improving performance in basketball. Therefore, the aim of this study was to assess the relationships between physical fitness, with food habits and nutritional knowledge in basketballers. Twenty-three healthy youth players to the same elite basketball academy participated in this study. Basketballers performed a basketball fitness test battery including jumping tests [countermovement jump (CMJ) and drop jump (DJ)]; 5, 10 and 20 m-linear sprints; change of direction (COD) tests [Lane Agility Drill test and 505 test], and repeated change-of-direction (RCOD) sprint and completed a Turconi questionnaire based on eating habits and nutritional knowledge. While no significant (p>0.05) correlations were found between physical fitness attributes and total score obtained in sections C and H in dietary questionnaire, significant correlations (r=0.606-0.971; large - nearly perfect; p<0.001 - 0.003) were found among jumping, COD, RCOD and LSST tests. These findings suggest that physical performance of youth basketball players is not influenced by their level of dietary behaviors and nutritional knowledge.